Design and Implementation of Elderly Health Monitoring Glasses Based on Intelligent Vision - Liu, Fangfei; Zhang, Zeyuan; Zhi, Xin; Wang, Hongyi; Yang, Chunlei (International Journal of Computer Science and Information Technology, 2025)
With the acceleration of the aging process in China, the elderly generally face the double challenges of eyesight decline and health care. Traditional health monitoring devices require extra wear and are complex to operate, making it difficult to meet daily needs. Therefore, this study innovatively combined the health monitoring function with daily glasses, and proposed a design scheme of elderly health monitoring glasses based on intelligent vision. Through the deep integration of the micro sensor and intelligent algorithm, based on preserving the function of vision correction, the non-inductive monitoring of vital signs such as heart rate and blood oxygen is realized, and the multi-modal pose analysis technology is used to identify the fall behavior in real time and automatically trigger the emergency help mechanism. The system adopts lightweight structure and voice interaction design to ensure that elderly users "ready to wear and use" and effectively solve the pain points of "cumbersome operation" of traditional equipment. The program uses daily wearable devices as the carrier to build an invisible health management system, provide new ideas for smart elderly care, and significantly improve the safety and independence of life for the elderly.